S. Weir Mitchell, 1829–1914: Philadelphia's Literary Physician - Cervetti, Nancy (Penn State Series in the History of the Book, 2012)
This modern biography provides a comprehensive and balanced view of a legendary figure in American medicine. Controversial because of his fierce fight against women’s rights, Mitchell achieved stunning success through his experimentation with venomous snakes, treatment of Civil War soldiers with phantom limbs and burning pain, and creation of the rest cure to treat hysteria and neurasthenia. Mitchell’s life was extraordinary—interesting in its own right and as a case study in the larger inquiry into nineteenth-century medicine and culture.